Personality and Job Satisfaction: The Impacts of Extraversion/Introversion on Job satisfaction of Chinese Employees - SU, CUIHONG (2017)
This study aims to identify the influences of personality (i.e. extraversion and introversion) on job satisfaction of Chinese enterprise’s employees. This study also compares the extraverts’ job satisfaction to introverts’ job satisfaction in numerous facets of general job satisfaction. Data were collected from a sample of 159 Chinese employee by online questionnaires. This study adopted the E-scale of the Chinese version of Eysenck Personality Questionnaire (EPQ-RSC) to measure personality traits of participants, and a 20-item scale for satisfaction measuring. There are two major findings of this study: 1) Personality has a significant impact on job satisfaction of Chinese employees, based on the result of regression analysis (F=939.031, p<0.05); 2) The satisfaction level of extraverted employees and introverted employees showed significant differences in all six facets of job satisfaction, based on the independent sample T-test. Moreover, extraverted employees tend to have higher job satisfaction than introverted employees. The possible reasons behind the findings are elaborated. Some implications from the findings for organizational practices, such as interventions to manage job satisfaction, employee development/training and personnel decision in recruitment and selection, have been critically recommended. Some limitations of this study and recommendation for future researches are provided.